Struktur Modal sebagai Moderating pada Berbagai Faktor yang Mempengaruhi Solvabilitas Perusahaan - Noor Hasanah; Rachma Agustina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to present empirical evidence regarding the influence of asset structure, ownership structure, and sales growth moderated by capital structure on solvency. This is a quantitative research study. The research subjects are companies in the Building Construction sub-sector listed on the Indonesia Stock Exchange from 2019 to 2021. The sample selection utilized purposive sampling, resulting in 15 companies that met the criteria and were observed over a period of 3 years. The data used in this research are secondary data derived from the companies' annual reports. For data analysis, descriptive statistical analysis techniques and data tests using SmartPLS 3.00 were employed. Based on the hypothesis test results, this research indicates that the variables of asset structure (X1), ownership structure (X2), and sales growth (X3) do not have a significant impact on solvency (Y). This can be observed in the case of (X1) towards (Y) where the obtained P-Value is 0.953 > 0.05, and t-value is 0.059 < 1.96. Similarly, (X2) towards (Y) shows a P-Value of 0.904 > 0.05, and t-value is 0.120 < 1.96. Additionally, (X3) towards (Y) reveals a P-Value of 0.966 > 0.05, and t-value is 0.043 < 1.96. Furthermore, the capital structure (Z) does not have the ability to moderate the influence of asset structure (X1), ownership structure (X2), and sales growth (X3) on solvency (Y). This can be observed in the case of (X2.Z) towards (Y) where the P-Value is 0.858 > 0.05, and t-value is 0.179 < 1.96, as well as (X3.Z) towards (Y) with a P-Value of 0.486 > 0.05 and t-value of 0.697 < 1.96. Conversely, capital structure (Z) has a significant impact on solvency (Y), as evident from the P-Value of 0.000 > 0.05 and t-value of 4.210 < 1.96.